Mutation patterns in gyrA and parC genes of ciprofloxacin resistant isolates of Neisseria gonorrhoeae from India. Issue 6 (1st December 2002) - Chaudhry, U; Ray, K; Bala, M; Saluja, D
Abstract : Aim: To analyse mutations in the gyr A and par C genes leading to possible increase in ciprofloxacin resistance (high MIC values for ciprofloxacin) in clinical isolates of Neisseria gonorrhoeae in Delhi, India. Method: MIC of ciprofloxacin for 63 clinical isolates of N gonorrhoeae were examined by the Etest method. Subsequently, gyr A and par C genes of these isolates were amplified and sequenced for possible mutations. Results: Out of the 63 clinical isolates tested, only five (8%) isolates were found to be susceptible to ciprofloxacin (MIC <0.06 μg/ml). DNA sequence analysis of the gyr A and the par C genes of all these isolates (n = 63) revealed that all isolates which were not susceptible to ciprofloxacin (n=58) had mutation(s) in gyr A and par C genes. 12 isolates (19%) exhibited high resistance with an MIC for ciprofloxacin of 32 μg/ml. Two out of these 12 isolates (UD62 and UD63), harboured triple mutations (Ser-91 to Phe, Asp-95 to Asn and Val-120 to Leu) in the gyr A gene. The third mutation of Val-120 to Leu, lies downstream of the quinolone resistance determining region (QRDR) of the gyr A and has not been described before in gonococcus. In addition, both these isolates had a Phe-100 to Tyr substitution in the par C, a hitherto unknown mutation. Conclusions: Emergence of ciprofloxacin resistance with high levels of MIC values (up to 32 μg/ml) in India is alarming. Double and triple mutations in gyr A alone or together in gyr A and par C could be responsible for such a high resistance.